Observation of B0s→D[bar]0K0S and evidence for B0s→D[bar]∗0K0S decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; et al. (Physical review letters, 2016)
The first observation of the B0s→¯D0K0S decay mode and evidence for the B0s→¯D*0K0S decay mode are reported. The data sample corresponds to an integrated luminosity of 3.0 fb−1 collected in pp collisions by LHCb at center-of-mass energies of 7 and 8 TeV. The branching fractions are measured to be B(B0s→¯D0¯K0)=[4.3±0.5(stat)±0.3(syst)±0.3(frag)±0.6(norm)]×10−4,B(B0s→¯D*0¯K0)=[2.8±1.0(stat)±0.3(syst)±0.2(frag)±0.4(norm)]×10−4,where the uncertainties are due to contributions coming from statistical precision, systematic effects, and the precision of two external inputs, the ratio fs/fd and the branching fraction of B0→¯D0K0S, which is used as a calibration channel.
*LHCb Collaboration: R. Aaij, P. D'Argent, S. Bachmann, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, S. Esen, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kecke, M. Kolpin, K. Kreplin, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Stahl, U. Uwer, M. Vesterinen, A. Zhelezov [und 705 weitere Personen]
Im Titel sind die Zahl 0 und das Zeichen * hochgestellt
Im Titel ist der Buchstabe s tiefgestellt
Im Titel steht der Buchstabe D mit einem Oberstrich
Gesehen am 10.07.2020